2016
DOI: 10.1016/j.jallcom.2015.12.189
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of La2B2O7(B Zr, Sn, Hf and Ge) pyrochlore: First-principles calculations

Abstract: Using first-principles theory and further verified by the experimental results, we have studied the electronic structure, mechanical and thermal properties of La 2 B 2 O 7 (B=Zr, Sn, Hf and Ge) pyrochlore. It is shown that the La 2 B 2 O 7 pyrochlore are charge-transfer-type insulators with the strong ionic bonding. The calculated band gap of La 2 Zr 2 O 7 , La 2 Sn 2 O 7 , La 2 Hf 2 O 7 , and La 2 Ge 2 O 7 are 4.01, 3.05, 3.13 and 2.42 eV, respectively. The elastic constants, hardness, shear modulus, bulk mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 27 publications
3
19
1
Order By: Relevance
“…As compared with the experimental measurement, our calculated elastic moduli for Gd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are overestimated slightly. This may be resulted from the employed LDA method, which generally underestimates the lattice constant whereas overestimates the mechanical modulus 41 . Besides, the defects and impurities in the sample experimentally may also lead to the underestimated values of the B and G 41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As compared with the experimental measurement, our calculated elastic moduli for Gd 2 Zr 2 O 7 and Sm 2 Zr 2 O 7 are overestimated slightly. This may be resulted from the employed LDA method, which generally underestimates the lattice constant whereas overestimates the mechanical modulus 41 . Besides, the defects and impurities in the sample experimentally may also lead to the underestimated values of the B and G 41 .…”
Section: Resultsmentioning
confidence: 99%
“…This may be resulted from the employed LDA method, which generally underestimates the lattice constant whereas overestimates the mechanical modulus 41 . Besides, the defects and impurities in the sample experimentally may also lead to the underestimated values of the B and G 41 . Variation of the elastic moduli for Sm y Gd 2-y Zr 2 O 7 and Gd 2 Sm y Zr 2-y O 7 with the Sm content is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the former, first-principles calculations were used in the study of defect formation in the pyrochlore structure, while for the latter thermodynamic properties were simulated using both the molecular dynamics method [11] and ab initio calculations [13][14][15]. For both applications, it was found that pyrochlore zirconates are generally favorable over titanates, hence more theoretical investigations on the lattice dynamics of zirconates have been carried out.…”
Section: Introductionmentioning
confidence: 99%
“…1000°C was chosen. In case of X-ray diffraction analysis, the pyrochlore compounds occur as defective fluorite and can be exchanged for cerium oxide because the pyrochlore structure is closely related to the fluorite structure and can be thought of as a cation-ordered anion deficient fluorite lattice, in which the cations form a face-centered cubic array [17]. In the database for the evaluation of the composition studied compounds samples were often compared with cubic CeO 2 (lattice parameter a = 0.5411 nm) [18].…”
Section: Resultsmentioning
confidence: 99%